Construction of a nursing management program for early fluid resuscitation in patients with acute pancreatitis: a Delphi study in China - Fang He; Xiaohong Zhang; Jiao Liu; Shaojian Mo; Lei Zhang; Xifeng Fu; Yanzhang Tian; Fei Gao; Yan Liu (BMC Nursing)
Abstract Aim and objectives To construct a set of scientific and feasible nursing management protocols for early fluid resuscitation in acute pancreatitis (AP) patients that can be used to guide clinical practice and enhance the treatment efficacy in these patients. Background Fluid resuscitation is a key means of early treatment for AP patients and has become a clinical consensus. Nurses are important practitioners of fluid resuscitation, and there is a lack of specific enforceable nursing management programs. Methods Through literature research, on-site research, semi-structured interviews, and other preliminary preparations of the first draft of the nursing management program for early fluid resuscitation in acute pancreatitis, the Delphi method was used to conduct two rounds of correspondence with medical and nursing experts, and then statistically analyzed. Results Fifteen and 14 questionnaires were distributed in two rounds, respectively, and 15 and 14 questionnaires were recovered, respectively. The positive coefficient of experts was 100%, the authority coefficient was 0.970 and 0.975, respectively; the coefficient of variation coefficient was 0.05–0.21 and 0.00–0.20, respectively; the expert coordination coefficients of all levels of indices in this study are 0.166–0.335 and 0.189–0.364, respectively. The P values of the first, second, and third level indices are < 0.05 according to the test of Kendall’s harmony coefficient. A total of 5 primary indicators, 11 secondary indicators, and 36 tertiary indicators were used to construct the Nursing Management Program for Early Fluid Resuscitation in Acute Pancreatitis. Conclusions The constructed nursing management plan for early fluid resuscitation in acute pancreatitis patients puts forward clear requirements and standards for nursing care in the early stage of AP treatment. This plan is scientific, represent good clinical practice, are feasible for nurses to follow, and construct a standardized protocol for the management of early fluid resuscitation in patients with acute pancreatitis.